Analisis Mutu Pengelolaan Obat di Puskesmas Kota Tegal - Cholilah Cholilah; Tri Wijayanti; Satibi Satibi (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2021)
Primary health centers is a facility that organizes health efforts at the first level to achieve health degrees, but in its implementation is still constrained in realizing standard pharmaceutical services. The purpose of the research is to find out the quality of drug management in Tegal City primary Health Center. This study is a non-experimental descriptive study. The study was conducted throughout the primary health center in Tegal City. Data collection is prospective and retrospective by tracing documents to obtain secondary data and direct observations, interviews of pharmaceutical personnel, heads of primary health centers, and heads of the pharmaceutical section to obtain primary data. The next drug management indicator is done descriptive data analysis by calculating the value of the indicator with the formula then compared to the standard and inter primary health care. Indicators of drug management used 28 and those that meet standard 10. Indicator results include conformity of items with disease patterns 76.39%, planning accuracy 321.10%, the accuracy of the number of requests 169.84%, the storage of narcotics 72.92%, the storage of drugs without contamination 98.97%, the storage of high alert drugs 68.15%, the storage of LASA drugs 87.5%, ITOR 1.87 times /year, the availability of drugs 36.08 months, drug items less than 14.01%, safe drug items 37.94%, excess stock items 41.76%, non-prescribed drugs 4.59% and drug value ED 3.85%. These results show that drug management indicators in Tegal City primary health centers have not been efficient and need improvements ranging from the planning stage to control. Indicators that still need improvement include ITOR and all indicators of drug availability. Things that need to be done to improve indicators that have not been efficient include increasing the number and quality of pharmaceutical human resources in primary health centers, increasing supervision of drug use and control, building communication, and a good organizing culture in primary health centers.